2008
DOI: 10.1227/01.neu.0000324732.36396.e9
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Extratemporal Epilepsy Surgery Experience of a Single Center

Abstract: Our results indicate that extratemporal epilepsy surgery at the Bethel Epilepsy Center has become more effective in the treatment of extratemporal epilepsy patients over the years, ensuring continuous improvement in outcome. This improvement can be attributed mainly to more restrictive patient selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 49 publications
3
35
0
1
Order By: Relevance
“…Pathological findings are typically reported in small-scale studies from individual centers, [13][14][15][16] or buried in larger series containing a full spectrum of patients among which only a small number was MRI-negative. 17,18 A few attempts at meta-analysis have been performed to better understand surgical outcome and factors such as pathology, surgery type, and seizure semiology in MRI-negative patients. Ansari et al 24 reported 95 pediatric extratemporal nonlesional epilepsy patients from 17 studies, and classified surgical pathology into three categories: cortical dysplasia, gliosis, and others (neuronal loss, encephalitis, polymicrogyria, ulegyria, chronic inflammation, and normal).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathological findings are typically reported in small-scale studies from individual centers, [13][14][15][16] or buried in larger series containing a full spectrum of patients among which only a small number was MRI-negative. 17,18 A few attempts at meta-analysis have been performed to better understand surgical outcome and factors such as pathology, surgery type, and seizure semiology in MRI-negative patients. Ansari et al 24 reported 95 pediatric extratemporal nonlesional epilepsy patients from 17 studies, and classified surgical pathology into three categories: cortical dysplasia, gliosis, and others (neuronal loss, encephalitis, polymicrogyria, ulegyria, chronic inflammation, and normal).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Studies specifically on the surgical pathology of MRI-negative patients, however, are limited to small-scale experiences of individual centers, [13][14][15][16] or cases buried in larger series containing both MRI-positive and -negative patients. 17,18 Moreover, with the advance in MRI technology over the last decade and the establishment of more uniform epilepsy MRI protocols, the definition of 'MRInegative' cases in recent studies may not be equivalent to earlier ones. The purpose of this study is to systematically review one institution's recent experience with the pathological substrates underlying strictly defined MRI-negative epilepsies.…”
mentioning
confidence: 99%
“…Presently, about half of these patients become suitable candidates for epilepsy surgery [6]. Surgery achieves long-term control in 50–80% of patients [7,8,9]. The gap between the patients who are suitable candidates for epilepsy surgery and those with drug-resistant epilepsy is becoming narrower, especially with the development of better imaging modalities (both structural and functional), brain-mapping techniques, microneurosurgical techniques and a better understanding of neurobiology of epilepsy [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although improvements in surgical outcome of patients with extratemporal epilepsy have been reported in recent years -mostly due to refinements in patient selection, seizure recurrence following this procedure is still high in comparison to patients operated for temporal epilepsy 22,23 . Pragmatically speaking, thus, we did not find differences in the occurrence of SUDEP in connection with post-surgical seizure status, neither in patients with temporal lobe nor in those with extratemporal lobe epilepsy.…”
Section: Discussionmentioning
confidence: 99%